Knockout of Hyaluronan Synthase 1, but not 3, Impairs Formation of the Retrocalcaneal Bursa - Sikes, Katie J. (J Orthop Res, 2018)
Hyaluronan (HA), a high molecular weight non-sulfated glycosaminoglycan, is an integral component of the extracellular matrix of developing and mature connective tissues including tendon. There are few published reports quantifying HA content during tendon growth and maturation, or detailing its effects on the mechanical properties of the tendon extracellular matrix. Therefore, the goal of the current study was to examine the role of HA synthesis during post-natal skeletal growth and maturation, and its influence on tendon structure and biomechanical function. For this purpose, the morphological, biochemical, and mechanical properties of Achilles tendons from wild type (WT) and hyaluronan synthase 1 and 3 deficient mouse strains (Has1(−/−) (Has1KO), Has3(−/−) (Has3KO), and Has1(-/−)3(−/−) (Has1/3KO)) were determined at 4, 8, and 12 weeks of age. Overall, HAS-deficient mice did not show any marked differences from WT mice in Achilles tendon morphology or in the HA and chondroitin/dermatan sulfate (CS/DS) contents. However, HAS1-deficiency (in the single or Has1/3 double KO) impeded post-natal formation of the retrocalcaneal bursa, implicating HAS1 in regulating HA metabolism by cells lining the bursal cavity. Together, these data suggest that HA metabolism via HAS1 and HAS3 does not markedly influence the extracellular matrix structure or function of the tendon body, but plays a role in the formation/maintenance of peritendinous bursa. Additional studies are warranted to elucidate the relationship of HA and CS/DS metabolism to tendon healing and repair in-vivo.